Supporting our supervisors: sending out an SOS. (14th October 2016) - Milne, Derek L.; Reiser, Robert
Abstract: In this Introduction to the Special Issue of the Cognitive Behaviour Therapist on clinical supervision we start by highlighting the unmet and overdue need for coherent organizational systems to support, guide and develop clinical supervisors. We identify a seven-step, cyclical model that describes how such a system might work, with particular reference to CBT supervision. These steps start with conceptualization (e.g. definition of CBT supervision) and complete the problem-solving cycle with evaluation (e.g. corrective feedback). We provide an overview of typical research and development activity for each part of this model to illustrate how a sound supervision infrastructure might best be developed. The SOS model provides a systematic approach to indicate the organizational conditions under which CBT supervision might flourish.